A Study And Analysis Of Consumers Buying Behaviour In Jammu And Kashmir - Dr Ajaz Ahmad Bhat (HM Journals, 2021)
This paper is going to Emphasize the behaviour of the consumers and their perception overthe shopping from the retailers at different area of two districts Anantnag and SrinagarJammu and Kashmir if we glance over the world wide consumers are treated as the realking of the markets either on the wholesale level or at the retailer level it is all by theorientation of the consumer whatever consumer demands market should present the sameat the right place on the right price to the general public, this will be like turning toolspoint for the business world in this paper, research will focus and present the perceptionand on behaviour related traits of consumers over the different marketing places , a wellformed questionnaire is prepared to find out the real facts and figures in a organised wayfor the data collection on the basis of the followings objectives like to study or examineabout the perception of consumers over the retail markets of two districts of Jammu andKashmir which will be based on Random sampling and to be distributed thequestionnaires among the 250 respondents via both modes online and offline toorespectively to cognize and to assess the objectives of the study in this research study oneof the statistical tools to be applied like chi square test for checking the significance of thereliability of the data and Analysis of the data like percentile method, average method alsoto be done with the help of SPSS software.